Fostering tenure security for forest landscape restoration in Ethiopia: Creating enabling conditions for the 2018 Forest Proclamation - McLain, Rebecca; Kassa, Habtemariam; Lawry, Steven; Yazew, Belay (Center for International Forestry Research, 2019)
A critical review of federal land law in order to align it with the 2018 Forest Law, together with the corresponding regional land laws, will greatly facilitate implementation of the national forest law that recognizes community rights to forests. However, actualizing rights on the ground requires strong political commitment and administrative support, and the existence of fair, secure, stable and accountable tenure systems. For this to happen, the state will need to fulfill its responsibilities of monitoring and regulating forest resource access and use, a task that will require strengthening communication and coordination across governance scales and sectors. Communities will need to strengthen their social networks, by building links with other forest-dependent communities and external organizations that can support them in their efforts to exert their forest rights. The goal and the challenge for Ethiopia’s current forest reform effort is to get the balance right between communities and the state in terms of how rights and governance functions are distributed, to enable the government to adapt to its new roles and ensure that communities receive the support they need to actualize their rights and discharge their forest management responsibilities as per agreed-upon management plans.